Differential Vulnerability of Oculomotor Versus Hypoglossal Nucleus During ALS: Involvement of PACAP - Maugeri, Grazia; D’Amico, Agata Grazia; Morello, Giovanna; Reglodi, Dora; Cavallaro, Sebastiano; D’Agata, Velia (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a progressive multifactorial disease characterized by the loss of motor neurons (MNs). Not all MNs undergo degeneration: neurons of the oculomotor nucleus, which regulate eye movements, are less vulnerable compared to hypoglossal nucleus MNs. Several molecular studies have been performed to understand the different vulnerability of these MNs. Through microarray technology, the differential genomic pattern between the two nuclei has been profiled. Among identified genes, adenylate cyclase activating polypeptide 1 (ADCYAP1) gene, encoding for pituitary adenylate cyclase-activating polypeptide (PACAP), was found significantly up-regulated in the oculomotor versus hypoglossal nucleus suggesting that it could play a trophic effect on MNs in ALS. In the present review, some aspects regarding the different vulnerability of oculomotor and hypoglossal nucleus to degeneration will be summarized. The distribution and potential role of PACAP on these MNs both in physiological conditions and in ALS will be discussed.